Parity of Human Values in the Islamic Thought Research (Journal of the College of Education for Women, 2019)
Human values are the most important concepts that the interest of society has to relay on these conceptual values. Any society will not be stabilized unless adheres to the right principles and values, all nations need such principles and values to stabilize. If any society doesn’t implement the human values that monotheistic religions urges equality between human, the far the society from the religious principles, the less there would be valence between human. The valence is urgent necessity in the current time. The far people get away from values and principles, the more they lose their freedom and dignity, therefore individual has to live with dignity and respect through the adherence to these values and principles. Apparently, equality between people is a reflection of justice. Therefore, justice would make life of society gets straight and put everything in the right place, that means respecting the right of others and comply with the laws so that people can live in security. Both development and progressive go on line with justice. The more justice prevails, the more people believe and convictions are related to sincere and hard work, and there would be more development in the society. Such society would calls for harmonization and obedience. It is possible to fulfill human valence in all aspects of life such as social life, political, economic, education, and religion. If and only if every individual has a commitment to higher value that would ennoble him/her to higher positions. It is also the implementation of the principles of Islamic Sharia which implies equality between human kinds. Islamic religion command and urges justice, it is also defined the rules and methods of the way that humanity would follow as well as the believer. Such believer has to comply with the principles of Islamic religion.